2012
DOI: 10.1371/journal.pone.0045980
|View full text |Cite
|
Sign up to set email alerts
|

“Because Somebody Cared about Me. That's How It Changed Things”: Homeless, Chronically Ill Patients’ Perspectives on Case Management

Abstract: BackgroundCase management programs for chronically ill, homeless people improve health and resource utilization by linking patients with case managers focused on improving management of medical and psychosocial problems. Little is known about participants’ perspectives on case management interventions.MethodsThis qualitative study used in-depth, one-on-one interviews to understand the impact of a case management program from the perspective of participants. A standardized interview guide with open-ended questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 34 publications
2
52
0
1
Order By: Relevance
“…Many of the existing qualitative analyses were designed to evaluate and inform aspects of interventions, such as low-barrier housing. 21,26,27,42,43 Participants in these studies may differ from ours because all agreed to participate in interventions, were receiving specialized services or housing, and were identified primarily through community rather than hospital referral. Yet these and other studies provide important insight into how structured, supportive environments and various means of approaching these individuals and caring for them helps to empower them by addressing factors that have contributed to their loss of self-identity and selfdetermination.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Many of the existing qualitative analyses were designed to evaluate and inform aspects of interventions, such as low-barrier housing. 21,26,27,42,43 Participants in these studies may differ from ours because all agreed to participate in interventions, were receiving specialized services or housing, and were identified primarily through community rather than hospital referral. Yet these and other studies provide important insight into how structured, supportive environments and various means of approaching these individuals and caring for them helps to empower them by addressing factors that have contributed to their loss of self-identity and selfdetermination.…”
Section: Discussionmentioning
confidence: 98%
“…Yet these and other studies provide important insight into how structured, supportive environments and various means of approaching these individuals and caring for them helps to empower them by addressing factors that have contributed to their loss of self-identity and selfdetermination. 21,[23][24][25][26][27]44 Other researchers have explored the perspectives of medical professionals and others who encounter this population rather than directly studying the individuals of interest. 45,46 Incorporating a wide range of different perspectives through purposive sampling and exploring negative cases that may contradict prevailing theories strengthened our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional qualitative shelter-based intensive case management research study done by Davis, Tamayo & Fernandez (2012) demonstrated the benefits of the strong interpersonal relationship these patients had with their case manager. This relationship was the overwhelming self-reported key to recovery for homeless persons with mental health and substance abuse issues (Davis et al, 2012).…”
Section: Cost-effectiveness Of Case Managementmentioning
confidence: 99%
“…This relationship was the overwhelming self-reported key to recovery for homeless persons with mental health and substance abuse issues (Davis et al, 2012). Research done on the Transitional Care model of case management is reported to reduce re-admissions but -intuitively so, does little to improve long-term outcomes (Volland, Schraeder, Sheldon & Hess, 2013).…”
Section: Cost-effectiveness Of Case Managementmentioning
confidence: 99%